The effects of propolis on doxorubicin-induced hepatorenal damage: a comparison of ethanolic and oily extracts of propolis - Selma Cirrik; Emel Kabartan Cokelİ; Emine Gulceri Gulec Peker; Gulay Hacioglu (CyTA - Journal of Food, 2023)
ABSTRACTThe protective effect of ethanolic propolis extract (PE) in the toxic effects of doxorubicin (DOX), a chemotherapy drug, has been reported previously. Since ethanol usage has some restrictions, in the present study, olive oil as an alternative to ethanol has been tested in DOX-induced hepatorenal injury and the effectiveness of the two extracts were compared. Male rats were orally given PE or oily propolis extract (PO) for 15 days (50 mg/kg/day) and DOX was injected (15 mg/kg, intraperitoneally) on the 13th day. The animals were sacrificed and then hepatorenal oxidative stress and functional parameters were evaluated. DOX-induced reduction in hepatorenal functions and oxidative stress were significantly reduced in both propolis treatment groups. Treatment with PO was more effective in reducing DOX-induced oxidative stress, yet both extracts showed similar efficacy in improving hepatorenal functions. We suggest that the PO could be preferred to avoid the side effects of ethanol.